Validity of Blood Pressure Measurement in Hypertention Patients - Merdekawati, Diah; Dasuki, Dasuki; Aguspairi, Aguspairi (Jurnal Ilmiah Ners Indonesia, 2024)
Hypertension is abnormal blood pressure and should measure more than once. Precise blood pressure measurements will produce valid data. This research aims to determine the validity of blood pressure in hypertensive patients. The method is quantitative with a cross-sectional research design, sampling technique using accidental, namely as many as 153 respondents, at the Rawasari Community Health Center, Jambi City, and the kappa test is used to statistical test. The validity of the measurement uses accuracy, specificity, and sensitivity tests. The results obtained were 66% of respondents with degree 1 hypertension on the right arm and 58.8% on the left arm. Blood pressure in the right arm correlates with blood pressure in the left arm and vice versa with values of p = 0.000. The sensitivity value is 73.2%, the specificity value is 88.7%, and the accuracy value is 83%. But the left arm has a sensitivity value of 78.8%, a specificity value of 85.1%, and an accuracy value of 83%. Blood pressure measurement on the right arm is more valid than the left arm because it has a higher specificity and positive predictive value and has a higher LR+ value. The conclusion is that the right arm is better for measuring blood pressure.